Tạo dựng lòng tin cho người tiêu dùng trực tuyến: Vai trò của các nguồn thông tin và tác động điều tiết của kinh nghiệm mua sắm trực tuyến - Hồ Trọng Nghĩa (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2018)
This study aims to investigate the role of two main information sources in online shopping context, which are word-of-mouth provided by customers and official information provided by e-tailers, in building customer’s cognitive and affective trust. Based on online trust literature, the research model is proposed and validated by surveying 503 online customers in Ho Chi Minh city. Structural Equation Modelling technique is adopted to analyze the collected data. The research results indicate the positive influence of the information sources on online trust including both cognitive and affective path. Besides, both cognitive and affective components of trust are positive predictors of online consumers’ repurchase intention. In addition, the moderating effect of online shopping experience is also validated.
Keywords: Online shopping; Cognitive trust; Affective trust; Information